Conceptual modeling for the design of intelligent and emergent information systems. (15th October 2016) - Fayoumi, Amjad; Loucopoulos, Pericles
Highlights: A multi-perspective conceptual modeling approach. Co-development of enterprise and information systems. Combining enterprise modeling techniques, design rationale and system dynamics. The utility of the approach is demonstrated though a case study. Abstract: A key requirement to today's fast changing economic environment is the ability of organizations to adapt dynamically in an effective and efficient manner. Information and Communication Technologies play a crucially important role in addressing such adaptation requirements. The notion of `intelligent software' has emerged as a means by which enterprises can respond to changes in a reactive manner but also to explore, in a pro-active manner, possibilities for new business models. The development of such software systems demands analysis, design and implementation paradigms that recognize the need for `co-development' of these systems with enterprise goals, processes and capabilities. The work presented in this paper is motivated by this need and to this end it proposes a paradigm that recognizes co-development as a knowledge-based activity. The proposed solution is based on a multi-perspective modeling approach that involves (i) modeling key aspects of the enterprise, (ii) reasoning about design choices and (iii) supporting strategic decision-making through simulations. The utility of the approach is demonstrated though a case study in the field of marketing for a start-up company.